Doomed to failure? - Pal, Parthapratim; Prakash, Shravani (2005)
There are far too many outstanding issues relating to the Doha Round that have to be solved during the run-up to the Hong Kong ministerial meeting of the WTO in December. The sheer number that will be on the agenda for this meeting make it a likely candidate for a failure. - Reproduced.
Keywords: World Trade Organization